IL‐17C amplifies epithelial inflammation in human psoriasis and atopic eczema. (19th January 2020) - Lauffer, F.; Jargosch, M.; Baghin, V.; Krause, L.; Kempf, W.; Absmaier‐Kijak, M.; Morelli, M.; Madonna, S.; Marsais, F.; Lepescheux, L.; Albanesi, C.; Müller, N.S.; et al.
Abstract: Background: Key pathogenic events of psoriasis and atopic eczema (AE) are misguided immune reactions of the skin. IL‐17C is an epithelial‐derived cytokine, whose impact on skin inflammation is unclear. Objective: We sought to characterize the role of IL‐17C in human ISD. Methods: IL‐17C gene and protein expression was assessed by immunohistochemistry and transcriptome analysis. Primary human keratinocytes were stimulated and expression of cytokines chemokines was determined by qRT‐PCR and luminex assay. Neutrophil migration towards supernatant of stimulated keratinocytes was assessed. IL‐17C was depleted using a new IL‐17C‐specific antibody (MOR106) in murine models of psoriasis (IL‐23 injection model) and AE (MC903 model) as well as in human skin biopsies of psoriasis and AE. Effects on cell influx (mouse models) and gene expression (human explant cultures) were determined. Results: Expression of IL‐17C mRNA and protein was elevated in various ISD. We demonstrate that IL‐17C potentiates the expression of innate cytokines, antimicrobial peptides (IL‐36G, S100A7 and HBD2) and chemokines (CXCL8, CXCL10, CCL5 and VEGF) and the autocrine induction of IL‐17C in keratinocytes. Cell‐free supernatant of keratinocytes stimulated with IL‐17C was strongly chemotactic for neutrophils, thus demonstrating a critical role for IL‐17C in immune cell recruitment. IL‐17C depletion significantly reduced cell numbers of T cells, neutrophils and eosinophils in murine models of psoriasis and AE and led to a significant downregulation of inflammatory mediators in human skin biopsies of psoriasis and AE ex vivo. Conclusion: IL‐17C amplifies epithelial inflammation in Th2 and Th17 dominated skin inflammation and represents a promising target for the treatment of ISD.